Non-native grass invasion drives biodiversity loss after a single fire in a semi-arid shrubland - Mahood, Adam L.; Balch, Jennifer K.; Barnard, David M.; Suding, Katherine N.; Chambers, Jeanne C. (Biological conservation, 2025)
In the Great Basin of the western United States, annual grass invasion has initiated a novel grass-fire cycle that has transformed vast areas of semi-arid shrublands into non-native annual grasslands that now burn frequently. After the initial transformation, the system is so fire prone that it is difficult to find areas that have not burned repeatedly. We evaluated how the ecosystem responds in the absence of repeated fire to determine if management interventions preventing it could be used to restore the native shrubland. We created a regional-scale chronosequence of areas that burned only once from 1984 to 2017 using Landsat-derived burned area products, and collected species composition data across a gradient of 4–32 years since fire. We used linear mixed models to look for evidence of native plant recovery, and used indirect gradient analysis and joint species distribution models to examine the response of species occurrence to a) fire occurrence and timing and pre- and post-fire climate; and b) topography, grazing, and annual grass dominance. Native diversity and perennial herbaceous cover were unrelated to time since fire and negatively associated with annual grass cover. The occurrence of a single fire had mostly negative associations with native species and mostly positive associations with non-native species. Grazing intensity did not affect the dominant post-fire annual grass, but non-native annual forbs sorted along a gradient towards two groups based on grazing intensity, annual grass cover, and topography. Annual grass competition will likely maintain the post-fire invasive-dominated plant community even if management interventions successfully stop the grass-fire cycle.